PENGARUH KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI STRUKTUR MODAL TERHADAP KINERJA KEUANGAN - Khoirunnisa Cahya Firdarini; Manendha Meganitri Kundala (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aimed to examines the effect of capital structure to financial performance with audit committee as moderating variable in consumer goods companies listed in BEI (Bursa Efek Indonesia) from 2016-2020. Capital structure measured with Debt to Equity Ratio (DER) and Debt to Assets Ratio (DTA).Based on purposive sampling method, total sample of this research is 180 firm-years. Hypothesis testing used is path analysis with AMOS v 23. The result show that Debt to Equity Ratio and Debt to Assets Ratio positive and significance influence to financial performance and audit committee as moderation variable have positive effect among Debt to Equity Ratio to financial performance but it have not effect among Debt to Equity Ratio to financial performance because audit committe only focuses on efectiveness assets used and assume that liability or debt is reasonable for consumer goods industries that have fast moving characteristic.